Comparison of the effects and side effects of misoprostol and oxytocin in the postpartum period: A systematic review - Zümrüt Bilgin; Nuran Kömürcü (Elsevier, 2019)
Follow-up of the side effects of uterotonics used for postpartum hemorrhage is one of the most important roles of health care providers. In this review, it is aimed to compare the side effects of misoprostol and oxytocin that are used to prevent postpartum hemorrhage. This systematic review was carried out in accordance with the guidelines for the Center for Reviews and Dissemination 2009 (CRD). Articles published in the PubMed, CINAHL, Wiley Interscience, Science Direct and Cochrane databases between 2010 and 2016 were examined. Finally, although 2277 articles were found to be related to misoprostol and oxytocin, only 12 randomized controlled (n = 6290) articles were included in the review. Results: In the misoprostol group, the rate of >500 mL blood loss was lower than that in the oxytocin group (p < 0.05). The groups were similar in terms of ≥500 mL blood loss were similar (p > 0.05). Although misoprostol was more effective than oxytocin in preventing PPH, the side effects of misoprostol were more. The incidence of drug-induced shivering, nausea and increase in body temperature were significantly higher in the misoprostol group than the oxytocin and placebo groups (p < 0.05). Shivering was most frequently seen in the 600 mg of sublingual misoprostol group (56.4%).Severe side effects of uterotonics used to prevent postpartum hemorrhage on maternal health were determined. Nurses and midwives should be aware of the side effects of uterotonic drugs and should develop care guidelines that explain the interventions to be performed in case of side effects. Keywords: Hb, Nursing and midwifery care, Postpartum blood loss, Randomized controlled study, Side effects of misoprostol and oxytocin